Networks and landscapes: a framework for setting goals and evaluating performance at the large landscape scale. Issue 3 (4th April 2016) - Bixler, R Patrick; Johnson, Shawn; Emerson, Kirk; Nabatchi, Tina; Reuling, Melly; Curtin, Charles; Romolini, Michele; Grove, J Morgan
Abstract : The objective of large landscape conservation is to mitigate complex ecological problems through interventions at multiple and overlapping scales. Implementation requires coordination among a diverse network of individuals and organizations to integrate local‐scale conservation activities with broad‐scale goals. This requires an understanding of the governance options and how governance regimes achieve objectives or provide performance evaluation across both space and time. However, empirical assessments measuring network‐governance performance in large landscape conservation are limited. We describe a well‐established large landscape conservation network in North America, the Roundtable on the Crown of the Continent, to explore the application of a social–ecological performance evaluation framework. Systematic approaches to setting goals, tracking progress, and collecting data for feedback can help guide adaptation. Applying the established framework to our case study provides a means of evaluating the effectiveness of network governance in large landscape conservation.